The Impact of Family Sustainable Livelihood and Environmental Cognition on Herdsmen’s Choice of Production Behavior - Qihang Wang; Yinjia Miao (Advances in Materials Science and Engineering)
This study analyzed the influence of sustainable livelihood and environmental cognition on herdsmen’s production behaviors on basis of logistic model. The consequences illustrated that the social capital followed by material capital, financial capital, and human capital has the greatest impact on herdsmen’s production behaviors, but the natural capital played a vital role in promoting herdsmen’s choice of raising breeding scale. The area and quality of grassland in herdsman families’ sustainable livelihood could encourage herdsmen to increase breeding scale, while the quantity of livestock, structure of house, the number of labor, the level of education, the status of health, and the income of families could promote herdsmen to restrain the breeding scale. The cognition of policy and ecological environment also had a significant positive effect on herdsmen restraining breeding scale.